The relationship between shyness and students' social anxiety using the mediating role of perceived fear of failure and stress - Sima Alizadeh (مدیریت و چشم انداز آموزش, 2021)
Extended AbstractAbstractThe aim of this study was to investigate the mediating role of fear of failure and perceived stress in the relationship between shyness and social anxiety of Payame Noor University students in Marand branch. The research method is essentially descriptive-correlative. The statistical population of the study consists of 6433 students of Payame Noor University, Marand Branch. The sample size of the study was 165 people by cluster random sampling. Cheek and Briggs (1990) Shyness Questionnaire, Cohen et al. (1983) Perceived Stress Questionnaire, Conroy Fear of Failure (2001) and Ilina (1996) Social Anxiety Questionnaire were used to collect data. Its authenticity was confirmed by the supervisor and academic experts and its reliability was also confirmed by Cronbach''''s alpha coefficient test. In order to analyze the data, the structural equation technique was used using Lisrel statistical software and Spss statistical software. Findings show that students with high perceived stress due to extreme self-assessment of their performance and that their main focus is on the negative aspects of events that happen to them are more likely to develop shyness. Due to high fear of not Acceptance and fear of being criticized by others, these people experience more shyness than people with low self-criticism. IntroductionExcessive fear, anxiety, and abnormal behaviors associated with these symptoms are common and main features of anxiety disorders. In the absence of danger or despite the insignificant danger, the person in these disorders feels that there is a great danger lurking, so it is strongly aroused physiologically and emotionally (Akrami, Nazhvani Shirvani, Zamani, 2020). Perceived stress is one of the major problems of human society and a great number of people are struggling with it. Stress seems to be an essential component and an inevitable result of human interaction with the environment. Stress involves the physical, mental, and emotional reactions that are experienced as a result of changes and needs in a person''''s life. Changes can be large or small. People respond differently to life changes. Positive stress can be a motivator, while negative stress can occur when these changes and needs fail. Perceived stress is a psychological state or process in which a person perceives his or her physical and psychological well-being as threatening. In other words, perceived stress is a person''''s perceived abilities and reassurance in the face of environmental demands. Stresses related to education has a greater impact on students'''' stress levels than stressors related to emotional and health relationships (Talebzadeh, Shahreiari, 2019). Social anxiety disorder is an extreme or unusual fear of situations in which a person''''s behavior or performance may be examined or evaluated by others. Social anxiety is a distressing or stressful feeling that is difficult to describe and control and that one experiences when one is in a social situation. People with social anxiety disorder have many psycho-social problems and this disorder has negative effects on their social, educational, occupational and mental performance (Haghayegh, Mosavi, 2019). Shyness is a painful feeling that is associated with many psychological problems, including aggression, depression, physical disorder, anxiety, obsessive-compulsive disorder, interpersonal sensitivity, personality disorders, drug use, post-traumatic stress disorder, and low self-esteem. Gilbert and Tanji (1998), edited by Gilbert and Miles, 2000) argue that the experience of criticism, understanding social status, and blame styles play an important role in shyness and social anxiety. They also believe that criticism and social setbacks can lead to feelings of shyness, especially if the person being criticized believes the criticism is correct and realizes that its undesirable and unattractive aspects have been observed by others (Doost Mohammadi, 2020). Higher education organizations such as Payame Noor University of, Marand Branch are one of the most important and key organizations in training knowledge-based human resources. Therefore, it is very important to pay attention to the correct category of education and keep students from the existing margins that cause damage to their educational process. Given that shyness is very common in today''''s societies, especially among adolescents and young people, so paying attention to this category and controlling it is very important. According to the contents of this study, an attempt is made to answer the question of whether fear of failure and perceived stress play a mediating role in the relationship between shyness and social anxiety of students of Payame Noor University, Marand Branch? Theoretical framework Educational technology is the analysis of learning problems and methods and the design, development, implementation, evaluation and management of educational and non-educational processes and resources to improve learning and performance in various educational centers, special training environments and job centers. Using technology for education is a way that higher education organizations such as Payame Noor University, Marand Branch is one of the most important and key organizations in training knowledge-based human resources. Therefore, it is very important to pay attention to the correct category of education and keep students from the existing margins that cause damage to their educational process. Given that shyness is very common in today''''s societies, especially among adolescents and young people, paying attention to this category and controlling it is very important. Reese''''s (2011) research showed that shyness has a mediating effect between self-criticism on variables based on social support, positive and negative life events, and satisfaction in close relationships, and in turn, provides the conditions to help contribute to the symptoms of depression.MethodologyThe present study was a descriptive correlative study. The statistical population of this study consists of 6433 students of Payame Noor University, Marand Branch. In the end, 163 responses were selected as the final sample size. The method of sampling is cluster random. To collect data related to the shyness variable, the Check and Brigger Questionnaire, Cohen et al. (1983) Questionnaire of Assessing Fear of Failure in Conroy Performance (2001) and Ilina (1996) Social Anxiety Questionnaire has been used.. Descriptive statistics (frequency, percentage, mean and standard deviation) was accomplished by SPSS 22 software, and to test the research hypotheses, first Kolmogorov-Smirnov test was used to check the normality of the research data distribution and then the structural equation technique by LISREL statistical software was used.Discussion and Results"t-value" is used to evaluate the significance of the relationship between variables. Since significance is checked at the error level of 0.05, if the amount of observed factor loads is calculated by t-value test is less than 1.96, the relationship is not significant and will be displayed in red in LISREL software. The standard factor load of confirmatory factor analysis to measure the strength of the relationship between each factor (hidden variable) and its visible variables (questionnaire items) in all cases is greater than 0.3. Therefore, the operating structure of the questionnaire will be confirmed.The standard factor load of confirmatory factor analysis to measure the strength of the relationship between each factor (hidden variable) and its visible variables (questionnaire items) in all cases is greater than 0.3. Therefore, the operating structure of the questionnaire will be confirmed. After calculating the standard operating load, a significant test should be performed. Based on the results observed in Figure (2), the factor load of t-statistic of the measurement indices of each of the studied dimensions at the 5% confidence level is greater than 1.96. The standard factor load of confirmatory factor analysis to measure the strength of the relationship between each factor (hidden variable) and its visible variables (questionnaire items) in all cases is greater than 0.3. Therefore, the operating structure of the questionnaire will be confirmed.The standard factor load of confirmatory factor analysis to measure the strength of the relationship between each factor (hidden variable) and its visible variables (questionnaire items) in all cases is greater than 0.3. Therefore, the operating structure of the questionnaire will be confirmed. In order to investigate the mediating effect of fear of failure and perceived stress in the hypothesis in question, the direct effect of two structures with indirect effect in the case of mediating variables should be examined so that if the effect increases, the mediating effect can be considered acceptable. In the present hypothesis, the direct effect is 0.33. The indirect effect in the presence of the mediating variable of fear of failure is: 0.63 × 0.67 = 0.422Indirect effect in the presence of the mediating variable of perceived stress is: 0.59 × 0.64 = 0.377Due to the fact that the direct path effect is less than the indirect path, so the existence of mediating variables increases the fear of failure and perceived stress and the mediating role in the present hypothesis is confirmed.ConclusionThe research hypothesis assesses the mediating role of fear of failure and perceived stress in the relationship between shyness and social anxiety of students of Payame Noor University, Marand Branch. In the present hypothesis, the direct effect is 0.33. Due to the fact that the direct path effect is less than the indirect path, so the existence of a mediating variable increases the fear of failure and perceived stress and the mediating role in the present hypothesis is confirmed. The results of the research hypothesis test are consistent and supported by the research findings of (Doost Mohammadi, 2020., Samadi, et al. , 2018., Pirfalak, 2018., Ran & et al, 2018). The hypothesis test results explain that students with high perceived stress are more likely to develop shyness due to extreme self-assessment of their performance and that their main focus is on the negative aspects of what is happening to them. , Due to high fear of rejection and fear of being criticized by others, these people experience more shyness than people with low self-criticism. On the other hand, the fear of failure in affairs makes the person worry about losing the reputation of his friends, and this in turn will cause him to withdraw from the group of friends. Finally, given that reducing social anxiety can increase a person''''s ability to communicate well with others and reduce anxiety in social situations, social inhibitions, or interpersonal behaviors due to concerns about interpersonal evaluation; it can play a role in reducing shyness and its components.